Understanding good communication in ambulance pre-alerts to the emergency department: findings from a qualitative study of UK emergency services - Rachel O’Hara; Joanne Coster; Fiona C Sampson; Jaqui Long (BMJ Open)
Objectives Prehospital notifications (pre-alerts) enable emergency department (ED) staff to prepare for the arrival of patients requiring a time-critical response. Effective communication of the pre-alert is key to enabling the ED to prepare appropriately, but evidence on communication practices is lacking. We undertook qualitative research to understand how pre-alert communication may be improved to optimise the ED response for pre-alerted patients.Design, setting and participants Data collection took place within three UK Ambulance Services and six EDs between August 2022 and April 2023. We undertook semi-structured interviews with 34 ambulance and 40 ED staff and 156 hours non-participation observation of pre-alert practice (143 pre-alerts). Verbatim interview transcripts and observation notes were imported into NVivo and analysed using a thematic approach.Results We identified significant variation in how pre-alerts were communicated that influenced how effectively information was transferred. Ambulance and ED staff demonstrated a shared recognition that pre-alerts need to be communicated concisely, but both received minimal training in how to give and receive pre-alerts. Efficient pre-alerting was influenced by clinician experience and seniority. ED and ambulance clinicians following different information-sharing formats sometimes led to interruptions, information loss and tensions, particularly when an early ‘headline’ clinical concern had not been shared. Ambulance clinicians sometimes questioned the appropriateness of their pre-alert when ED clinicians did not explain the rationale for not giving the expected response (that is, being accepted into a high-priority area of the ED). Additional sources of frustration included technological problems and poor communication of estimated time of arrival and caller/responder identities.Conclusions Use of a shared format, including a headline ‘cause for concern’, may improve the clarity, usefulness and civility of pre-alerts, particularly when the clinician’s concern is not obvious from observations. Basic training on how to undertake pre-alerts for both ED and ambulance clinicians may improve understanding of the importance of pre-alert communication.Trial registration number ISRCTN12652860.